Interreligious Friendship after "Nostra Aetate." Editor's Response - Tiemeier, Tracy Sayuki (2016)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966916000529/resource/name/firstPage-S0360966916000529a.jpg